2020
DOI: 10.1038/s41598-020-78333-y
|View full text |Cite
|
Sign up to set email alerts
|

A study of red blood cell alloimmunization and autoimmunization among 200 multitransfused Egyptian β thalassemia patients

Abstract: The development of hemolytic erythrocyte alloantibodies and autoantibodies complicates transfusion therapy in thalassemia patients. These antibodies ultimately increase the need for blood and intensify transfusion complications. There is a scanty data on the frequency of RBC alloimmunization and autoimmunization in Egyptian β thalassemia patients as pretransfusion antibody screening is not routinely performed. We studied the frequency of alloimmunization and autoimmunization among 200 multiply transfused β tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 56 publications
5
19
4
Order By: Relevance
“…Similarly, in this study, the M and N antigens were observed with higher frequencies of 82.4% and 62.7% respectively in beta-thalassemia patients. However, in comparison, El-Beshlawy et al from Egypt reported much lower frequencies of M and N antigens at 8.14% and 1.16% respectively [30]. Our study results have variations among blood group antigens and different hematological diseases especially in beta-thalassemia due to genetic differences among different ethnic groups.…”
Section: Discussioncontrasting
confidence: 59%
“…Similarly, in this study, the M and N antigens were observed with higher frequencies of 82.4% and 62.7% respectively in beta-thalassemia patients. However, in comparison, El-Beshlawy et al from Egypt reported much lower frequencies of M and N antigens at 8.14% and 1.16% respectively [30]. Our study results have variations among blood group antigens and different hematological diseases especially in beta-thalassemia due to genetic differences among different ethnic groups.…”
Section: Discussioncontrasting
confidence: 59%
“…Overall, autoAb frequency ranges from 1% to 28.2% in β-thalassemia [ 17 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], from 0.8% to 42% in SCD [ 27 , 28 , 29 , 30 ], and reaches 61% in HS (likely due to more sensitive technique) [ 11 ]. Few data are available about the Ab type, with warm antibodies (IgG+) being reported in half of the DAT-positive cases, IgG+ complement (C)—in approximately one third of cases, and C+—in the remaining cases.…”
Section: Resultsmentioning
confidence: 99%
“…Thalassemia is another hemoglobinopathy that requires chronic transfusion therapy. Alloantibodies occur in 5-30% of thalassemia patients, and are more common after splenectomy, long duration of treatment and frequent transfusion [61][62][63][64]. The dominant antibodies are against the Rh and Kell groups, each comprises 20-30% of the antibodies [64].…”
Section: Non-abo Blood Groups Incompatibilitymentioning
confidence: 99%
“…Alloantibodies occur in 5-30% of thalassemia patients, and are more common after splenectomy, long duration of treatment and frequent transfusion [61][62][63][64]. The dominant antibodies are against the Rh and Kell groups, each comprises 20-30% of the antibodies [64]. When prophylactically transfusing Rh (D, C, E) and K antigen matched RBC units, alloantibodies were still detected in 32.5% of patients, with an alloimmunization rate of 0.26 antibodies/100 units, and 72.5% of antibodies were directed against Rh [63].…”
Section: Non-abo Blood Groups Incompatibilitymentioning
confidence: 99%
See 1 more Smart Citation